Genetic testing for assessment of lynch syndrome in young patients with polyps. Issue 12 (December 2021) - Laish, Ido; Goldberg, Yael; Friedman, Eitan; Kedar, Inbal; Katz, Lior; Levi, Zohar; Gingold-Belfer, Rachel; Kopylov, Uri; Feldman, Dan; Levi-Reznick, Gili; Half, Elizabeth
Abstract: Background: Routine screening for establishing Lynch syndrome (LS) in young individuals diagnosed with adenomas is not recommended due to its low yield, and limited sensitivity of the employment of immunohistochemistry for DNA mismatch-repair proteins on polyps. Hence we aimed to evaluate the yield of germline mutational analysis in diagnosis of LS in a young Israeli cohort with colorectal adenomatous polyps. Methods: Data were retrospectively collected on consecutive patients, age ≤ 45 years, who underwent colonoscopy with removal of at least one adenoma during 2015–2020, and subsequently genetic testing by multigene panel or LS-Jewish founder mutation panel. Results: Overall, 92 patients were included (median age 35 years, range 23–45 years), of whom 79 (85.8%) underwent multigene panel genotyping, and 13 (14.2%) analysis for Jewish founder LS gene mutations. Altogether, 18 patients were identified with pathogenic mutations in actionable genes, including LS-associated genes in 6 (6.5%), BRCA2 in 2 (2.5%), GREM1 in 1(1.2%), and low-penetrance genes- APC I1307K and CHEK2- in 9 (11.4%) patients. Compared with non-LS patients, LS-carriers had a significantly higher median PREMM5 score (2.6 vs. 1.3; P = 0.04). Conclusions: Young individuals diagnosed with adenomatous polyps should be offered genetic testing when fulfilling clinical guidelines for LS, but weight should also be given to adenoma characteristics in the PREMM5 score.